MG132 Ameliorates Kidney Lesions by Inhibiting the Degradation of Smad7 in Streptozotocin-Induced Diabetic Nephropathy - Chenlin Gao; Keri Aqie; Jianhua Zhu; Guo Chen; Ling Xu; Lan Jiang; Yong Xu (Journal of Diabetes Research)
Background. Smad7 is the main negative regulatory protein in the transforming growth factor-β (TGF-β) downstream signaling pathway, which plays an important role in diabetic nephropathy (DN) and may be related to the ubiquitin proteasome pathway (UPP). Aim. We investigated the role of UPP in regulating TGF-β/SMAD signaling and explored the therapeutic effect of the ubiquitin proteasome inhibitor MG132 on DN. Methods. Wistar rats were randomly divided into a diabetes group and a normal control group. Rats in the diabetes group were injected intraperitoneally with streptozotocin. Diabetic rats were then randomly divided into a diabetic nephropathy group (DN group), an MG132 high concentration (MH) group, and an MG132 low concentration (ML) group. After 8 weeks of treatment, 24-hour urinary microalbumin (UAlb), urinary protein/urinary creatinine (Up/Ucr) values, ALT, AST, Bcr, kidney damage, TGF-β, Smad7, fibronectin (FN), and Smurf2 were detected. Results. The body mass and Smad7 protein expression decreased in DN group, but kidney weight, kidney weight index, UAlb, Up/Ucr, FN and Smurf2 mRNA expression, and TGF-β protein expression increased. However, these changes diminished following treatment with MG132, and a more pronounced effect was evident in MH group compared to ML group. Conclusion. MG132 alleviates kidney damage by inhibiting Smad7 ubiquitin degradation and TGF-β activation in DN.